1988
DOI: 10.1007/bf00640668
|View full text |Cite
|
Sign up to set email alerts
|

The responses of the catecholamines and ?-endorphin to brief maximal exercise in man

Abstract: The responses to brief maximal exercise of 10 male subjects have been studied. During 30 s of exercise on a non-motorized treadmill, the mean power output (mean +/- SD) was 424.8 +/- 41.9 W, peak power 653.3 +/- 103.0 W and the distance covered was 167.3 +/- 9.7 m. In response to the exercise blood lactate concentrations increased from 0.60 +/- 0.26 to 13.46 +/- 1.71 mmol.l-1 (p less than 0.001) and blood glucose concentrations from 4.25 +/- 0.45 to 5.59 +/- 0.67 mmol.l-1 (p less than 0.001). The severe nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…In the present study the reduced concentration of plasma catecholamines These observations may explain the high negative correlations between blood pH and plasma adrenaline concentrations that have been reported following short-term maximal continuous exercise (Cheetham et al, 19;Brooks et al, 1988;Nevill et al, 1989). Despite the high circulating levels of plasma adrenaline in the placebo condition, the degree of hyperglycaemia in venous blood was not different between experimental conditions.…”
Section: Discussionsupporting
confidence: 55%
“…In the present study the reduced concentration of plasma catecholamines These observations may explain the high negative correlations between blood pH and plasma adrenaline concentrations that have been reported following short-term maximal continuous exercise (Cheetham et al, 19;Brooks et al, 1988;Nevill et al, 1989). Despite the high circulating levels of plasma adrenaline in the placebo condition, the degree of hyperglycaemia in venous blood was not different between experimental conditions.…”
Section: Discussionsupporting
confidence: 55%
“…We have confirmed the results obtained in previous studies [9,36], which showed exercise to induce an increase of ~-endorphin, and have found that nifedipine-SR neither stimulates nor inhibits ~-endorphin release. The precise role of ~-endorphin is not clear.…”
Section: Discussionsupporting
confidence: 81%
“…Nevertheless, it is obvious that both exercise duration and exercise intensity are important determinants of the plasma [CA] response in this type of exercise, as they have also been found in endurance exercise (Kjaer 1989 (Brooks et al 1988(Brooks et al , 1990Cheetham et al 1986;Gratas-Delamarche et al 1994;Schwarz and Kindermann 1990). …”
Section: Discussionmentioning
confidence: 98%
“…However, it has been found that the plasma [A] increase in heavy anaerobic exercise may be higher than in aerobic exercise (Kindermann et al 1982: Schwarz andKindermann 1990). Dierent maximal anaerobic activities such as sprinting (Cheetham et al 1986;Brooks et al 1988) and bicycling (Gaitanos et al 1993;Gratas-Delamarche et al 1994) as well as heavy resistance exercise training (Kraemer et al 1987) have indeed been found to elevate plasma [A] markedly.…”
Section: Introductionmentioning
confidence: 94%